Looking for locals under a closed-list proportional representation system: the case of Portugal - Espírito-Santo, A.; Sanches, E. (Electoral Studies, 2018)
Parties' motivation to include locals depends on the characteristics of the electoral system. This article analyzes where on the lists parties choose to position locals under closed-list proportional representation systems. Furthermore, it also investigates how that choice varies depending on two key district factors, namely district magnitude and whether or not the district is in a peripheral region. To that end, it draws on an original biographical data set of candidates for the Portuguese National Parliament (1983, 1995, 2002, 2005 and 2009). The findings show that there are fewer locals among the higher positions on the candidates' lists and among heads of lists. District magnitude and peripheral region effects go in the expected direction, but these effects are small.